Examining ecotourism intention: The role of tourists' traits and environmental concerns - Rafiq, Farrukh; Adil, Mohd; Wu, Jei-Zheng (Frontiers in Psychology, 2022)
The study offers new insights by examining the influence of personality traits (extraversion and neuroticism) on tourists' intentions to visit ecotourism sites using the lens of the theory of planned behavior. It also investigates whether environmental knowledge moderates the effect of extraversion, neuroticism, and environmental concern on tourists' ecotourism intentions. We applied structural equation modeling on 350 responses collected through the Amazon M-Turk platform. Results highlight that extroverts are more likely to express ecotourism intentions than neurotic tourists. However, it was also noted that neurotic tourists' intention to visit ecotourism sites could be influenced if their environmental concerns were emphasized. The study offers important new insights to managers, policy-makers, and practitioners about the roles of personality traits, environmental knowledge, and environmental concern vis-a-vis their relative significance in shaping tourists' decision-making and choices for ecotourism sites. As a result, managers/practitioners need to devise specific communication strategies to enhance awareness and a sense of responsibility among neurotic tourists.